Pemenuhan Hak Konsumen melalui Perlindungan Hak Merek - Dias Bintang Wibisono; Mozes Reynaldo Christanto (Universitas Negeri Surabaya, 2020)
If we studied deeper, fulfillment of consumer rights especially the right to comfort, security, and safety in consuming goods and or services; The right to choose goods and or services and to obtain goods and or services in accordance with the exchange rate and conditions and guarantees promised; The right to true, clear and honest information about the condition and guarantee of goods and services has a relationship with the trademarks protection. Trademark protection has been understood to be limited to the protection of trademark owners and there is no relationship between trademark and consumers. Though some of the rights received by consumers can actually be associated with the existence of a trademark protection.